Ball-contact injuries in 11 National Collegiate Athletic Association sports: The Injury Surveillance Program, 2009-2010 through 2014-2015 - Fraser, M. A.; Grooms, D. R.; Guskiewicz, K. M.; Kerr, Z. Y. (Journal of Athletic Training, 2017)
Context: Surveillance data regarding injuries caused by ball contact in collegiate athletes have not been well examined and are mostly limited to discussions of concussions and catastrophic injuries.